2020
DOI: 10.1177/1523422320949145
|View full text |Cite
|
Sign up to set email alerts
|

Self-Compassion and Resilience at Work: A Practice-Oriented Review

Abstract: The Problem A key challenge for human resource development (HRD) scholars and practitioners is to understand the individual competences that can be trained and developed to enhance employee resilience at work. Empirical evidence has been accumulated on the benefits of self-compassion—that is, a set of malleable states that can be developed through HRD interventions—for individual resilience, as well as on the factors that can strengthen self-compassion in organizations. Nonetheless, limited efforts have been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 70 publications
1
33
0
Order By: Relevance
“…Feeling that everyone experiences the same thing can make individuals not separate or isolate themselves from the environment when faced with specific difficulties (Smith, 2015). When feeling this, individuals will be more accepting of all the feelings they experience, and by doing so, individuals will do good to themselves when they are experiencing difficulties (Lefebvre et al, 2020). This can be explained by the research of Neff et al (2005), who found that students who have a self-compassionate attitude will be kinder to themselves when they experience failure, by being kind, they will become more aware that what they are going through is a typical experience for every student to experience.…”
Section: Resultsmentioning
confidence: 99%
“…Feeling that everyone experiences the same thing can make individuals not separate or isolate themselves from the environment when faced with specific difficulties (Smith, 2015). When feeling this, individuals will be more accepting of all the feelings they experience, and by doing so, individuals will do good to themselves when they are experiencing difficulties (Lefebvre et al, 2020). This can be explained by the research of Neff et al (2005), who found that students who have a self-compassionate attitude will be kinder to themselves when they experience failure, by being kind, they will become more aware that what they are going through is a typical experience for every student to experience.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Shapiro et al (2007) found that training in Mindfulness-Based Stress Reduction (MBSR) resulted in a significant increase in self-compassion. Different workplace components like personal factors, contemplative training and leadership styles have been identified that can foster self-compassion ( Lefebvre et al, 2020 ). Banker and Bhal (2020) identify different organizational pressures and enablers that affect the level of compassion.…”
Section: Discussionmentioning
confidence: 99%
“…As personal resilience impacts health care resilience, human resources management in companies (e.g., Lefebvre et al. 2020 ) and health care institutions (e.g., Hart et al. 2014 ; Jackson et al.…”
Section: Application Areas and Methodologies To Investigate Resiliencementioning
confidence: 99%